Clinical audit as a tool to optimize contracted private healthcare provision: Testing the waters in resource-deprived Greece. (March 2019) - Souliotis, Kyriakos; Golna, Christina; Mantzana, Vasiliki; Papaspyropoulos, Sotirios; Koutsovasilis, Anastasios; Sotiropoulos, Alexios
Background and Aims: Clinical audit is applied to optimize clinical practice and quality of healthcare services while controlling for money spent, critically in resource-deprived settings. This case study reports on the outcomes of a retrospective clinical audit on private hospitalizations, for which reimbursement had been pending by the Health Care Organization for Public Servants (OPAD) in Greece. This case study is the first effort by a social insurance organization in Greece to employ external clinical audit before settling contracted private healthcare charges. Methods: One thousand two hundred hospitalization records were reviewed retrospectively and a fully anonymized clinical audit summary report created for each one of them by a team of clinical audit experts, proposing evidence-based cuts in pending charges where medical services were deemed clinically unnecessary. These audit reports were then collated and analysed to test trends in overcharges among hospitalized insureds per reason for hospitalization. Results: The clinical audit report concluded that 17.4% of a total reimbursement claim of €12, 387, 702.18 should not be reimbursed, as it corresponded to unnecessary or not fully justifiable according to evidence-based, best practice, medical service provision. The majority of proposed cuts were related to charges for medical devices, which are borne directly by social insurance with no patient or private insurance co-payment. Conclusion: Clinical audit of hospital practice may be a key tool to optimize care provision, address supplier-induced demand and effectively manage costs for national health insurance, especially in circumstances of budgetary constraints, such as in austerity-stricken settings or developing national healthcare systems.